Courage tastes of blood : the Mapuche community of Nicolás Ailío and the Chilean state, 1906-2001 - Mallon, Florencia E., 1951- (Radical perspectives., 2005)
Follows the history of an indigenous community in southern Chile across the 20th century, using oral history and archival material to analyze the shifting relationship between the Mapuche people and the Chilean state.